2020
DOI: 10.32038/sem.2020.07.03
|View full text |Cite
|
Sign up to set email alerts
|

Croatian Teachers During COVID-19 Pandemic

Abstract: The teacher plays a central role in every education system. In addition to imparting knowledge and perfecting students’ skills, the teacher is also a role model on a socio-emotional, moral and speech level. However, its role has changed throughout history and depended on culture and lifestyle. Today, the education system around the world is facing a major test, and thus the role of the teacher as the central person of this process is being tested. Namely, the pandemic caused by the coronavirus switched teachin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…They found that by using Web 2.0 tools, students discarded their preconceptions, realised the benefits of using certain ICTs, and thus, increased the possibility of using those in their work. This is crucial in emergency situations and in times after a pandemic, as there is a possibility that some features of online distance education will remain in the future, which is also pointed out by Aladrović Slovaček and Matković [ 56 ], who suggest professional training for teachers. In addition, Khan et al [ 54 ] mention a training proposal for students as well.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations
“…They found that by using Web 2.0 tools, students discarded their preconceptions, realised the benefits of using certain ICTs, and thus, increased the possibility of using those in their work. This is crucial in emergency situations and in times after a pandemic, as there is a possibility that some features of online distance education will remain in the future, which is also pointed out by Aladrović Slovaček and Matković [ 56 ], who suggest professional training for teachers. In addition, Khan et al [ 54 ] mention a training proposal for students as well.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Many authors [ [56] , [57] , [58] , [59] ] state that one of the main problems of distance education in emergency situations lies with interaction and communication. On the one hand, Akachi and Ayed [ 59 ] as well as Yorkovsky and Levenberg [ 58 ] point out the importance of teaching certain areas (teaching entrepreneurship via authentic experiences, role-playing, workshops, etc.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations